Surrogate decision making in crisis - Wilkinson, Dominic (Journal of medical ethics, 2022)
Care of the critically ill newborn includes support for the birth mother/parents with regular updates around the clinical condition of the baby, and involvement in discussions around complex decision-making issues . Discussions around continuation or discontinuation of life-sustaining are challenging even in the most straightforward of cases, but what happens when the birth mother is critically unwell? Such cases can lead to uncertainty around who should assume the parental role for these difficult discussions . In this round table discussion, we explore the ethical, moral and legal uncertainties raised by coincident severe maternal and neonatal illness in the context of surrogacy.